Analisis Postur Kerja Dengan Metode Rapid Upper Limb Assessment (Rula) dan Nordic Body Map Pada Pekerja Produksi di PT. Jayamas Medica Industri Kab. Sidoarjo - Adini Anggun Risanti Putri; Ratna Ayu Ratriwardhani; Merry Sunaryo; Muslikha Nourma Rhomadhoni (Jurnal Ilmiah Wahana Pendidikan, 2022)
Musculoskeletal disorders (MSDs) are disorders of the skeletal muscles. According to the Bureau of Labor Statistics (BLS), there were 387,820 cases ofmusculoskeletal disorders (MSDs) from the total injuries and illnesses of workers in 2011. This study aims to analyze the level of risk, occupational risk at work. position using the Rapid Upper Limb Assessment (RULA) method. to production workers at PT. Jayamas Medica Industri, Sidoarjo Regency. This study used an analytic observational research design with a cross sectional approach. The population of this study are workers in the manufacturing section. The resulting sample is 29 using the Slovin formula and the sampling technique using a random sampling system. The variables of this research are personal and work factors, work posture, RULA method, and Nordic Body Map (NBM) questionnaire. This analytic data only generates the frequency and percent distribution of each variable and is interpreted as tables and stories. The results showed that most of the respondents complained about the lower neck as much as 79% and the upper neck as much as 69%. With this, the researchers calculated using the RULA method, the results obtained from the RULA method were respondents with serious complaints that needed further examination. Summarizing the results and discussing workers' complaints or disturbances, the recommended suggestions are stretching, designing the workplace according to the needs of workers, conducting training and socialization activities. Therefore, the researcher designed the workstation as a table and chair.